2007
DOI: 10.1002/cphc.200700134
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of a Discotic Liquid‐Crystalline Charge‐Transfer Complex

Abstract: The structure of the charge-transfer complex hexakis(n-hexyloxy)triphenylene-2,4,7-trinitro-9-fluorenone (HAT6-TNF) has been characterized by neutron scattering, X-ray diffraction (XRD), optical microscopy, and dielectric relaxation spectroscopy (DRS). On the basis of these data and the 1:1 stoichiometry, a consistent structure for the complex is proposed. This structure differs markedly from structures previously proposed for similar materials, because the TNF molecules are found to be situated between the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…We measured a skeletal density of 1.08 ± 0.01 g cm −3 for HAT6d-TNFd, corresponding to an increase in density of about 7% with respect to HAT6. 17 These observations indicate that the columnar morphology has drastically changed in the charge transfer compound. For a hexagonal columnar structure with the TNF sandwiched between the HAT6 molecules, the column−column distance should be about 17% smaller compared to pure HAT6.…”
Section: ■ Materials and Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…We measured a skeletal density of 1.08 ± 0.01 g cm −3 for HAT6d-TNFd, corresponding to an increase in density of about 7% with respect to HAT6. 17 These observations indicate that the columnar morphology has drastically changed in the charge transfer compound. For a hexagonal columnar structure with the TNF sandwiched between the HAT6 molecules, the column−column distance should be about 17% smaller compared to pure HAT6.…”
Section: ■ Materials and Methodsmentioning
confidence: 95%
“…Liquid-like motions due to "flip-flopping" of the dihedral angles between the carbons of the HAT6 tails occur on a comparable time scale for the CT complex and for pristine HAT6. 17,31 Second, a rapid buildup of spin polarization is observed for the core 13 C H (within 0.1 ms for both HAT6 and HAT6-TNF at ambient temperature) and for the TNF C−H carbons (within 1 ms), revealing a more rigid environment than for the tails. Third, the resolution in the proton dimension (e.g., Figure 6) for all HAT6 and TNF signals is quite good for the solid state MAS data sets collected without homonuclear decoupling during t 1 ( 1 H) evolution.…”
Section: ■ Materials and Methodsmentioning
confidence: 96%
“…Earlier efforts through NMR [6 -13], dielectric spectroscopy (DS) [11][12][13][14][15][16][17][18], neutron scattering [19,20], and computer simulations [20 -22] have shed light on the dynamics. The NMR studies identified (i) the main process as reflecting the axial motion of the discs around the columnar axis [6,11] and (ii) quasiperiodic regions of high and low packing density along the columns [8] as proposed by de Gennes [23].…”
mentioning
confidence: 99%
“…23,33 The charge transfer compounds were obtained by mixing HAT6 (or HAT6D) with 2,4,7-trinitro-9-fluorenone (TNF) in a 1:1 molar proportion in dichloromethane. 23 The mixture was subsequently evaporated to dryness at room temperature. To remove any traces of solvent and to ensure the correct phase behavior, the resulting composite was heated to the isotropization temperature, T = 237…”
Section: A Sample Preparationmentioning
confidence: 99%